The Measurement of Dielectric Properties of Medium Using Electromagnetic Waves - Naktong, Watcharaphon; Khasukorn, Yossawadee; Leokun, Chuthamani; Phapatanaburi, Khomdet; Santalunai, Samran; Santalunai, Nuchanart (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2025)
This research presents the development of a dielectric measurement system for metamaterials, using four different configurations of dielectric media. The system has two main parts: (1) a measurement setup with two horn antennas that work at 2.1 GHz along with a vector network analyzer (VNA), and (2) a signal processing unit created in MATLAB to calculate electrical parameters. Test results confirm that the system can estimate the relative permittivity ( ) in the range of 1.04 - 1.58 with an error margin not exceeding ±2 %, based on a comparison between measurements obtained from the proposed system and results from full-wave simulation using CST Microwave Studio. When comparing the performance of aluminum rod-based metamaterial structures, it was found that increasing the number of layers significantly expanded the transmission bandwidth to 1.65 - 2.50 GHz, corresponding to a fractional bandwidth of approximately 46 %. These are the results of the proposed approach in both the effective design of metamaterial structures and the development of a low-cost measurement system that serves as a practical alternative to expensive commercial dielectric measurement equipment.